Correlation between Individual Factors and Mental Workload with Work Fatigue in Nilam Terminal Surabaya - Andika Savira Putri; Endang Dwiyanti; Ahmad Rido'i Yuda Prayogi; Finda Istiqomah (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Work fatigue can be caused of excessive workload and work capacity such as age and tenure. This study aimed to analyze the strength of the correlation between individual factors and mental workload with work fatigue on the Surabaya Patchouli Terminal crane operator. Methods: The study design is a cross sectional. The sampling technique taken was total sampling so that all populations were a sample of 30 people, consisting of CC and RTG operators in Nilam Terminal Surabaya. The independent variables are individual factors including age and years of service obtained from the questionnaire, mental workload which is assessed based on the NASA-TLX questionnaire, while the dependent variable is work fatigue measured using a reaction timer. The collected data were then analyzed using the Spearman correlation. Results: The results show 23 operators (76.7%) experienced heavy work fatigue and 7 operators (23.3%) experienced moderate work fatigue. Conclusion: The strongest correlation is mental workload with work fatigue and the weakest correlation is age with work fatigue. Meanwhile, correlation tenure with work fatigue is in between. It is recommended to provide psychological consultation once a week for operators.